Strategi Transformasi Digital pada UMKM: Analisis Dampaknya terhadap Keberlanjutan Bisnis dan Keunggulan Bersaing - Mulyadi, Lintang (GEMA EKONOMI, 2024)
Digital transformation is a key factor in strengthening the competitiveness and sustainability of MSMEs in the technology-based economy era. Despite the significant contribution of MSMEs to the Indonesian economy, many business actors still face challenges such as limited digital literacy, access to capital, and organizational resistance. This study aims to analyze the influence of digital transformation strategies on business sustainability and competitive advantage of MSMEs in Indonesia. The research method used is a quantitative approach with an explanatory design, involving 150 MSME respondents from the trade, service, and manufacturing sectors in West Java. The research instrument was a questionnaire with a Likert scale, which was tested for validity and reliability before distribution. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that the level of digitalization has a significant effect on increasing turnover, operational efficiency, and market expansion. The main obstacles found were low digital literacy (44%) and limited capital (37%), which hamper the optimization of digital strategies. This study also found that MSMEs that are able to integrate digital technology with a sustainability orientation demonstrate better performance across economic, social, and environmental dimensions. The implications of this research emphasize the importance of government policy support in increasing digital capacity and access to technology-based financing, as well as the need for digital strategies tailored to the characteristics of each MSME sector.